25-Hydroxyvitamin D levels are related to hyperinsulinemia in polycystic ovary syndrome - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Aim: To determine 25-hydroxyvitamin D levels and the relationship between 25-hydroxyvitamin D and metabolic disturbances including insulin resistance in women with PCOS. Materials and methods: We compared biochemical, hormonal parameters and 25-hydroxyvitamin D levels of 58 women with PCOS and 38 body mass index matched controls. Results: There was no difference in 25-hydroxyvitamin D levels of women with PCOS and the control group. Low 25-hydroxyvitamin D levels in women with PCOS were related to higher insulin levels (r=-0.271 and p = 0.042). More than 90% of the subjects had hypovitaminosis D. The negative relationship between 25-hydroxyvitamin D levels and body mass index did not reach statistical significance. Conclusion: Low 25-hydroxyvitamin D levels were related to hyperinsulinemia in women with PCOS.
Keywords: Insulin resistance; obesity; polycystic ovary syndrome; vitamin D; INSULIN-RECEPTOR GENE; VITAMIN-D DEFICIENCY; HYPOVITAMINOSIS-D; RESISTANCE; WOMEN; OBESITY